Trouble with strangers : a study of ethics - Eagleton, Terry, 1943- (Chichester ; Malden, MA : Wiley-Blackwell Pub., 2009)
Trouble With Strangers represents a groundbreaking intervention in ethics by one of the world's most important theoreticians. It is written with Terry Eagleton's usual wit, panache, and uncanny ability to summarize and criticize otherwise complex philosophical and theoretical conversations. Eagleton breaks down ethical theories into three psychoanalytic categories of the imaginary, the symbolic, and the real, and applies this analysis to discussions of the work of central figures like Hutcheson, Kant, and Spinoza, as well as fascinating interpretations of Shakespeare. He also engages with contemporary continental ethics, particularly Levinas and Badiou, and goes on to examine the relation of ethics to politics. This is a must-have book for all readers of philosophy and theory, and anyone who has an interest in the important contemporary work of Terry Eagleton
-- The insistence of the imaginary -- Introduction: The mirror stage -- Sentiment and sensibility -- Francis Hutcheson and David Hume -- Edmund Burke and Adam Smith -- The sovereignty of the symbolic -- Introduction: The symbolic order -- Spinoza and the death of desire -- Kant and the moral law -- Law and desire in measure for measure -- The reign of the real -- Introduction: Pure desire -- Schopenhauer, Kierkegaard and Nietzsche -- Fictions of the real -- Levinas, Derrida and Badiou -- The banality of goodness
Includes bibliographical references and index
Keywords: Ethics